Coverage of the topic of artificial intelligence in the media: how to achieve the fourth industrial revolution (Herald of Journalism, 2024)
The article comprehensively reflects the problems of artificial intelligence in the media as an achievement of the fourth industrial revolution. We will study the influence of artificial intelligence on the media and the conditions of its interaction from a comparative perspective.Computer tools that mimic a person's individual mind and actions form the basis of artificial intelligence. This area began to develop as a separate scientific direction in the second half of the twentieth century. Its main activities were management, analysis, comparison, synthesis of information in society, proving the correctness of forecasts and assumptions and drawing conclusions.       The research article's purpose is to consider, through in-depth scientific analysis, the problems of artificial intelligence in the media as an achievement of Kazakhstan's fourth industrial revolution economic program policy.       The authors conducted chronological research by analyzing scientific and theoretical works and publications on artificial intelligence. The main scientific and theoretical values of the study include new ideas and conclusions about artificial intelligence. Definitions and scientific analyses by domestic and foreign scientists determining the role of artificial intelligence in the development of new technologies are described.       The authors of the article, who studied expert and analytical articles about artificial intelligence in traditional media, attempt to thoroughly investigate its dangers and benefits for society.       The results of the study can be used to promote practical work in the field of media and communication, its adaptation to new technologies and the implementation of effective strategic premises.
Keywords: media, artificial intelligence, fourth industrial revolution, GPS technology, Chat GPT neural network.